Pengaruh Family Empowerment Terhadap Kemampuan Deteksi Dini dan Perilaku Pencegahan Stunting di Pamekasan, Madura - Nur Mukarromah; Diah; Septian Galuh Winata; Erfan Rofiqi; Chlara Yunita Prabawati; Daviq Ayatulloh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The purpose of this study was to analyze the effect of family empowerment on the ability to detect early and prevent stunting. Methods: A quasy experiment study with two groups consisting of 66 respondents was recruited using purposive sampling. The family empowerment instrument uses the media module and the ability for early detection is measured using the The Stunting Tool for Early Prevention questionnaire and prevention behavior is measured using stunting prevention behavior. Data were analyzed using SPSS version 21 with the Wilcoxon Signed Rank and Mann Whitney Tests. The results showed that the ability of early detection and stunting prevention behavior showed an increase in the intervention group with good category (22.41 to 79.48 and 23.87 to 81.35, respectively). Results: The results of the significance test showed that family empowerment had a significant effect on early detection ability (p = 0.001) and stunting prevention behavior (p = 0.000). Conclusion: Early detection ability and stunting prevention behavior can be improved through family empowerment that specifically focuses on growth, nutritional status, knowledge, additional supplements, hygiene and discipline in posyandu activities